Clinical impact of serum α-fetoprotein and its relation on changes in liver fibrosis in hepatitis C virus patients receiving direct-acting antivirals. Issue 9 (September 2019) - Fouad, Rabab; Elsharkawy, Aisha; Abdel Alem, Shereen; El Kassas, Mohamed; Alboraie, Mohamed; Sweedy, Ahmad; Afify, Shimaa; Abdellatif, Zeinab; Khairy, Marwa; Esmat, Gamal
Abstract : Background: α-Fetoprotein (AFP) is used widely as a serological marker for hepatocellular carcinoma. However, the AFP value is elevated in chronic hepatitis C virus (HCV) patients without hepatocellular carcinoma. Yet, data on the impact of direct-acting antiviral agents (DAAs) therapy on AFP levels after viral eradication are still lacking. Aim: The aim of this study was to elucidate the changes in the serum AFP level in chronic hepatitis C patients treated with DAA-based therapy and their relation to response and liver fibrosis parameters. Patients and methods: A total of 456 chronic HCV patients who received different DAAs-based treatment regimens were enrolled. Laboratory data including serum AFP, transient elastography values, and fibrosis scores were recorded at baseline and sustained virological response at 24 weeks after treatment (SVR24). The outcome was the changes in the AFP level from baseline to SVR24 and its relation to changes in liver fibrosis parameters at SVR24 using Spearman's rank correlation test. Results: Overall, 96.9% of enrolled patients were responders. A statistically significant improvement in serum transaminases, albumin, transient elastography values, and fibrosis scores at SVR24 was reported. The AFP level was significantly decreased from a median (interquartile range) of 6 (3.2–10.8) ng/ml before DAAs to 4 (2.3–6) ng/ml at SVR24 ( P < 0.0001). Only 22.6% of patients showed an increase in the AFP level after treatment. On multivariate analysis, the only independent baseline variable associated with an increase in the AFP level after treatment was baseline AFP (odds ratio: 0.95, 95% confidence interval: 0.91–0.99, P = 0.02). There is a significant correlation between changes in AFP and liver fibrosis parameters at SVR24. Conclusion: DAAs-based regimens are a highly efficient antiviral therapy for chronic hepatitis C patients that resulted in improvements in the serum AFP level.